Presupposition in Heforshe Speech by Emma Watson’s on UN Campaign - Putri Aulia Said (ELITE: Journal of English Language and Literature, 2018)
This research is aimed at describing the presupposition used in HeForShe speech by Emma Watson’s on UN campaign. Yule’s theory of presupposition is used as a tool of analysis of the text of speech and sentence contained in the script of the Emma’s speech as data. Data are collected through watching the audio visual, reading the speech script, coding and note-taking, identifying and grouping, then analyzed through presenting, describing, and interpreting the data as well as  concluding the analysis. The result indicated that Emma Watson performs four (4) elements of presuppositions in HeForShe speech. They are existential presupposition, factive presupposition, lexical presupposition and structural presupposition. However, the most dominant type of presuppositions that appears in HeForShe speech by Emma Watson’s is existential presupposition. Existential presuppositions very frequently appear in utterances. It is logically if seeing the context of the speech that presented the existence of people or something involved in the issue of gender equality and also showed the existence of a movement for equality struggle. This is done by Watson to make the audiences believed that the issue of inequality is existed and it is worrying enough, so the changes are needed. Through the campaign, she is currently promoting, Watson hopes that the audience will participate in fighting for inequality through the unifying movement of the United Nations, in the label HeForShe.